Government-Directed Urban Growth, Firm Entry, and Industrial Land Prices in Chinese Cities - Jan K. Brueckner; Wenhua Liu; Wei Xiao; Junfu Zhang (Center for Economic Studies and ifo Institute (CESifo), 2022)
We examine the effect of a large-scale administrative reorganization in China, where counties are annexed into cities to accommodate urban growth. We present a simple model to illustrate how this annexation may affect firm entry decisions and in turn land market outcomes. Using nationwide data on land-lease transactions, we find that annexation raises industrial land prices in the annexed counties by 7 percent but does not reduce land prices in neighboring counties and central cities. We show that the annexed counties experienced increases in firm entry and investment, offering a plausible mechanism for the effect on industrial land prices.
Keywords: R11; R12; R14; R33; R58; 330; urban growth; industrial land prices; annexation; China